Application of "One Syndrome and One product" specialized nursing plan for pain management in the oncology ward ("一证一品"专科护理模式在肿瘤病房疼痛管理中的应用) - GUAN Li (关丽); WEI Shuting (魏书婷); HAO Li (郝丽) (Association of Integrative Nursing, 2021)
Objective To explore the application effect of "One Syndrome and One Product" specialized nursing plan for pain management in the oncology ward. Methods Taking the implementation time of the project as the dividing line, 50 cancer patients with hospital admission between Jan. 2017 and Dec. 2017 were included as the control group, and another 50 cancer patients with hospital admission between Jan. 2018 and Dec. 2018 were included as the study group. In the management of cancer pain symptoms, the combination of disease and syndrome, treatment and nursing, Traditional Chinese Medicine (TCM) and TCN nursing were reflected, the external treatment of TCM and emotional nursing were adopted, and the quality nursing ran through the whole process. The time to pain relief, the cognitive level of pain and patients' satisfaction were compared before and after the implementation of the project. Results After the implementation of the "One Syndrome and One Product" nursing project, the time to pain relief of patients in the study group shortened remarkably compared with that in the control group(P＜0. 05). The rate of patient awareness on pain related self-care knowledge was 100. 00%, and rate of patient satisfaction was 90. 00%. Conclusion Through the construction of specialized care ward based on "One Syndrome and One Product" nursing project, it can effectively help cancer patients relieve pain, improve the awareness rate of pain self-care knowledge, improve patient satisfaction, and improve the quality of nursing service. (目的 探讨"一证一品"专科护理模式在肿瘤病房疼痛症状管理中的应用效果。方法 以项目实施的时间为分界线, 采用便利抽样方法选取2017年1月-12月收入科室的50例肿瘤患者为对照组, 2018年1月12月收入科室的50例肿瘤患者为试验组。在肿瘤疼痛症状管理中体现"病与证"、"施治与施护"、"中医药与中医护理"相结合, 采用中医外治法及情志护理, 将品质护理贯穿全程。比较项目实施前后患者疼痛改善时间、对疼痛的认知水平及患者满意度的变化。结果 与对照组相比, 试验组患者的疼痛改善时间缩短(P＜0. 05)。试验组患者疼痛相关自我护理知识知晓率100. 00%, 满意度为90. 00%(45/50)。结论 通过"一证一品"专科护理示范病房建设, 在肿瘤患者疼痛症状管理中可以有效的帮助肿瘤患者缓解疼痛, 提高疼痛自我护理知识知晓率, 进而提高患者的满意度, 提升护理服务质量。)